Association of Interleukin-10 –592 C > A gene polymorphism with coronary artery disease: A case-control study and meta-analysis. (March 2021) - Ghalandari, Marzieh; Jamialahmadi, Khadijeh; Nik, Maryam Mardan; Pirhoushiaran, Maryam; Mirhafez, Seyed Reza; Rooki, Hassan; Avan, Amir; Ghazizadeh, Hamideh; Moohebati, Mohsen; Nohtani, Mahdi; Zaimkohan, Hooshang; Ferns, Gordon A.; et al.
Highlights: The cross-sectional study supports a significant association of IL-10 –592 C > A with CAD. The subjects carrying A allele had a significantly higher risk of CAD. The subjects carrying AA genotype had a significantly higher risk of CAD. The results of the meta -analysis showed a significant association between IL and 10 –592 C > A and CAD in the co-dominant model. Abstract: Background: Coronary-artery-disease (CAD) is the leading cause of death worldwide, and hence there is a need to identify reliable markers for identifying individuals at high risk of developing CAD. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that is associated with an increased risk of developing both atherosclerosis and acute coronary events. The study aimed to explore the association of a genetic variant in IL-10 with the risk of developing CAD and the severity of the disease. To further explore, a systematic review and meta -analysis was performed. The cumulative results of the relationship between IL and 10 –592 C > A polymorphism and CAD in Iranian population have also been presented. Methods: In this cross sectional study, a total of 948 individuals including 307 healthy controls and 641 patients that among cases, four hundred and fifty-five of the patients had > 50% stenosis (angiogram positive group) and 186 patients had < 50% stenosis (angiogram negative group) were recruited from the Mashhad-Stroke and Heart-Atherosclerotic-Disorders cohort. Genotyping for the IL-10 –592 C > A polymorphism was performed using a PCR-RFLP technique, and statistical analysis undertaken by univariate and multivariate analyses. PubMed, Google Scholar and Scopus were searched for papers related to this polymorphism up to October 2019. The Meta-analysis was done based on the random effect model using a Meta-analysis. Results: In our study, the frequency of the variant A allele of the IL-10 –592 C > A was significantly higher in CAD patients than the control group (P value = 0.043). Moreover, subjects carrying AA genotype had a significantly higher risk of CAD (OR: 1.8, 95%CI: 1.04–3.16), p = 0.03), compared to those with the wild type genotype. The results of meta -analysis of 9336 cases and 8461 controls did not also show any significant association between IL and 10 –592 C > A and CAD in dominant and recessive genetic models but only in co-dominant model when fix effect was applied. Conclusion: Although our research findings support a significant association of genetic polymorphism in the IL10 gene with cardiovascular diseases, this finding cannot be confirmed in meta -analysis. Further functional analysis and evaluation of this marker in a multicenter setting are needed to establish its value as a risk stratification marker.